Vitamin B12 for cognition - Malouf, R; Areosa Sastre, A (Cochrane Collaboration, 2003)
Background An association between neuropsychiatric disorders and vitamin B12 deficiency has been recognized since 1849 when pernicious anaemia was first described. It has been suggested that deficiency of vitamin B12 might contribute to age-associated cognitive impairment. Low serum vitamin B12 concentrations are found in more than 10% of older people. A high prevalence of low serum vitamin B12 levels, and other indicators of vitamin B12 deficiency have been reported among people with Alzheimer's disease. A review is needed of trials assessing effects of vitamin B12 supplementation on cognitive function in later life. Objectives To examine the effect of B12 supplementation on cognitive function of demented and elderly healthy people in terms of preventing the onset or progression of cognitive impairment or dementia. Search methods The trials were identified from a search of the Specialized Register of the Cochrane Dementia and Cognitive Improvement Group on 24 January 2006 using the terms B12, "B 12", B-12, B-complex, "B complex". In addition MEDLINE 1966 to 2006/01-week 3 and EMBASE 1980-2005/12 were searched to pick up studies with healthy volunteers. Selection criteria All randomized double-blind trials in which vitamin B12 at any dose was compared with placebo. Data collection and analysis Both reviewers applied the selection criteria to assess the quality of the studies. One reviewer (RM) collated and analysed the data. For each outcome measure data were sought on every patient randomized. Main results Three trials were included (De La Fourniere 1997; Hvas 2004; Seal 2002). One trial (Hvas 2004) reported follow-up results at 3 months after randomization, 2 months after treatment was completed; the data from this study were not combined with others. People with dementia and low serum vitamin B12 levels were recruited for the studies. The results showed no statistically significant evidence of a treatment effect of vitamin B12 supplementation compared with placebo, on cognitive function. Authors' conclusions Evidence of any efficacy of vitamin B12 in improving the cognitive function of people with dementia and low serum B12 levels is insufficient. The included trials (De La Fourniere 1997; Hvas 2004; Seal 2002) were restricted to a small number of patients with Alzheimer's disease and other types of cognitive impairment. No trials involving people without dementia or using other definitions of vitamin B12 deficiency were found.